BECOMING A TEACHER OF WRITING IN ELEMENTARY CLASSROOMS - Larson, Mindy Legard; Phillips, Donna Kalmbach ([S.l.] : ROUTLEDGE, 2024)
The Second Edition of Becoming a Teacher of Writing in Elementary Classrooms is an interactive learning experience focusing on all aspects of becoming-writer and teacher of writing in the Writing Studio. The Writing Studio is illustrated with authentic classroom scenarios and include descriptions of assessments, mini-lessons, mentor texts, and collaborative and individual teaching strategies. The parallel text, Becoming-Writer, allows readers to engage as writers while learning and applying writing process, practice, and craft of the Writing Studio. The new edition includes integration of preschool writers, multilingual learners, translanguaging, culturally sustaining pedagogy, social emotional learning, Universal Design for Learning and an updated companion website with teacher resources. This dynamic text supports teachers' agency in the ongoing journey of joyful teaching and writing.
Keywords: Language arts (Elementary); English language -- Composition and exercises -- Study and teaching (Elementary); Report writing -- Study and teaching (Elementary); LANGUAGE ARTS & DISCIPLINES / Literacy; EDUCATION / Teaching Methods & Materials / Arts & Humanities